Danger zone - The spermatic cord during anterior plating of the symphysis pubis. Issue 2 (February 2022) - Hörlesberger, Nina; Hohenberger, Gloria; Grechenig, Peter; Schwarz, Angelika; Grechenig, Christoph; Ornig, Martin; Tackner, Ellen; Gänsslen, Axel
Highlights: The spermatic cord is at risk during anterior plating of the symphysis, because of its close relation to the spermatic cord. Average distance between the palpable pubic tubercle and the spermatic cord are below one fingerbreadth. As anterior plating is not done very frequently, this fact must come into surgeons' minds. Abstract: Background: Distances between anatomic landmarks and anatomic structures at risk are often underestimated by surgeons. Purpose: The goal of the study was to evaluate the distances between anatomic landmarks and the spermatic cord in case of anterior plating of the symphysis. Methods: A total of 25 pelves (50 hemipelves) of male embalmed cadavers were dissected. A 5-hole 3.5mm locking compression plate (Synthes GmbH) was fixed from directly anterior on the symphysis. Measurements were taken 1) distance between the tips of both pubic tubercles, 2) horizontal interval between the lateral border of the plate and the medial margin of the SC (bilateral), 3) distances between the medial border of the SC and the tip of the pubic tubercle (bilateral), 4) distances between the medial border of the SC and the lateral basis of the pubic tubercle (bilateral). Results: The distance between the pubic tubercles was 60.3mm in average (SD: 5.7). The interval between the lateral border of the plate and the medial margin of the SC was on average 4.5mm (SD: 1.9) on the right and 4.7mm (SD: 2.6) on the left side. The distance between the tip of the pubic tubercle and the medial border of the SC was in average 11.2mm (SD: 2.7) on the right, and 11.0mm (SD: 2.7) on the left side. The average distance between the medial border of the SC and the lateral basis of the pubic tubercle was 8.1mm (SD: 2.4) on the right and 8.2 mm (SD: 2.4) on the left side. Conclusion: The SC is at risk not only during dissection but also during anterior plating of the symphysis, because of its close relation to the SC. Clinical Relevance: Average distances between the palpable pubic tubercle and the SC are below one finger breadth (as reference).